2014
DOI: 10.1111/inr.12155
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perceptions of patient safety culture in Jordanian hospitals

Abstract: Study results implied that improving patient safety culture requires a fundamental transformation of nurses' work environment. New policies to improve collaboration between units of hospitals would improve patients' safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
81
5
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 22 publications
18
81
5
4
Order By: Relevance
“…In the present study, the researchers found no significant difference in terms of marital status, gender, age, professional experience, education level and work hours with PSC in none of the hospitals. These results contradict those of Khater, Akhu‐Zaheya, Al‐Mahasneh, and Khater () in Jordan, who reported that as the number of total years of experience goes high, the nurse's perception of the PSC increases. Our findings also contrast the results of the other studies by Abdou and Saber () in Egypt and Jiang et al () in China.…”
Section: Discussioncontrasting
confidence: 79%
“…In the present study, the researchers found no significant difference in terms of marital status, gender, age, professional experience, education level and work hours with PSC in none of the hospitals. These results contradict those of Khater, Akhu‐Zaheya, Al‐Mahasneh, and Khater () in Jordan, who reported that as the number of total years of experience goes high, the nurse's perception of the PSC increases. Our findings also contrast the results of the other studies by Abdou and Saber () in Egypt and Jiang et al () in China.…”
Section: Discussioncontrasting
confidence: 79%
“…In contrast to other studies, this study (29) revealed no significant relationship between staff members' years of service and patient safety culture ratings. Like previous studies, all patient safety culture elements showed positive correlations with each other with one exception: there was no relationship between "frequency of events" and "management support," "teamwork within units," "teamwork across," "staffing, handoffs transitions" and "non-punitive responses" (29)(30)(31). similar to previous studies, "staffing" scored the lowest among all the patient safety culture elements (28) and "teamwork within units" (32,33) scored the highest in this study.…”
Section: Discussionsupporting
confidence: 63%
“…; Khater et al. ), and there were none in the Gaza Strip. Thus, there is limited knowledge about nurses’ perception of patient safety culture in this area.…”
Section: Introductionmentioning
confidence: 96%
“…Several studies have been conducted on patient safety culture in the Middle East region (Aboul-Fotouh et al 2012;El-Jardali et al 2014;Hamdan 2013;Najjar et al 2015). However, studies that focused on nurses only were limited (Alayed et al 2014;Ammouri et al 2015;Bahrami et al 2014;Khater et al 2015), and there were none in the Gaza Strip. Thus, there is limited knowledge about nurses' perception of patient safety culture in this area.…”
Section: Introductionmentioning
confidence: 99%